Asimetría fluctuante como herramienta para medir la inestabilidad en el desarrollo ocasionada por perturbaciones ambientales: una revisión del estado del arte en Anuros (2021)
The inability of a species to repeatedly and accurately produce the same phenotype when exposed to environmental conditions is known as developmental instability. Being able to identify those small deviations in a perfect bilateral organism can provide information about the environmental disturbances that occur throughout the development stage. One tool that can be used to establish this type of interaction is fluctuating asymmetry (FA), since it has the potential to reflect random deviations from bilateral symmetry. This has been widely studied in various groups of birds, mammals, insects, amphibians and plants, and has been used as a bioindicator to identify disturbances on habitats, whether of anthropogenic or natural origin. Anurans represent a good study model to make use of this tool, since they are a taxonomic group particularly sensitive to environmental disturbances. Characteristics of their physiology such as their permeable skin, their life history associated with bodies of water and their wide distribution...